Development of an observer of rotor angular velocity and resistance moment on the shaft of an adjustable permanent magnet synchronous motor powered through long cable - Alexander S. Glazyrin; Evgeniy I. Popov; Vladimir A. Kopyrin; Semen S. Popov; Evgeniy V. Bolovin; Vladimir Z. Kovalev; Rustam N. Khamitov; Vadim V. Timoshkin (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. Currently, when using submersible electric motors in centrifugal electric pump installations in cyclic operation mode, there is a reduction in the inter-repair period of submersible equipment, which is associated with a reduction in oil pumping periods to several minutes. As a result, there is a multiple increase in starting currents and torque, which leads to an increase in mechanical loads on the pump shaft and appearance of resonance phenomena during the electric motor acceleration, reducing the reliability of a seal protection. To solve these problems, it is necessary to synthesize closed-loop vector control systems with current and electromagnetic torque control in transient responses. Open-loop scalar control systems for electric drives of oil well production are used in operation, which is due to the complexity of obtaining feedback signals on the angular velocity of the rotor and the moment of resistance on the shaft by means of submersible telemetry. This problem determines the relevance and necessity of developing observers for rotor speed and load torque estimation, taking into account the features of the technological process of installing centrifugal electric pumps, in particular, the presence of a long cable for powering a submersible electric motor based on a synchronous machine with permanent magnets. Aim. To develop a full-order observer rotor speed and load torque for the dynamic system "long supply cable – synchronous motor with permanent magnets". Methods. System analysis and identification of dynamic systems, synthesis of Luenberger observers, mathematical modeling of dynamic systems, electric drives and electrical machines. Result and conclusions. The authors have proposed the mathematical model of a rotor speed and load torque full-order observer for the dynamic system "long supply cable – synchronous motor with permanent magnets". The performance of the observer was investigated under varying load on the shaft, mismatch of non-zero initial conditions, deviation of the parameters of the equivalent circuit of the observer and the object in the range from –20 to +20% of the nominal values.